Liberalism under Siege: The Political Thought of the French Doctrinaires - Craiutu, Aurelian (Lexington Books, 2003)
Liberalism under Siege: The Political Thought of the French Doctrinaries is a compelling examination of the French Doctrinaries, a largely neglected group of liberal thinkers in post-revolutionary France who were proponents of a nuanced sociological and historical approach to political theory. The first systematic interpretation of the French Doctrinaries' political writings to appear in English, Liberalism under Siege combines textual analysis and historical interpretation to explore the Doctrinaires' ideas on the French Revolution, democracy, political power, sovereignty of reason, publicity, capacity, and representative government. Aurelian Craiutu's detailed work is not only an argument for the reappraisal of the Bourbon Restoration as a golden age of political thought; it is also a passionate and persuasive addition to contemporary debates about the diversity of liberalism.